Direitos humanos e a formação de professores que ensinam Ciências - SOUZA, Ana Carla Santos de (2020)
Themes such as dignity of the human person, needs and human rights, as well as those related to principles and values such as freedom, respect, equality, justice and non-discrimination, among others, need to penetrate the spaces of teacher training, with the perspective of reaffirming and disseminate human rights principles. The research-training, developed in the context of the theme "Relations between Science, Society and Citizenship II", with the students of the Integrated Degree Course in Science, Mathematics and Language, at the Federal University of Pará, aimed apprehending as a formative experience, involving "the affirmation of human rights", contributes to the necessary problematization of its opposite "the violation of human rights". For this, we used photos reproductions that presented degrading situations with humans. We used photograph reproductions that presented degrading situations with human beings, to foment the problematization about the situations. We brought to this article the analysis of the appreciations of two graduates, regarding infantile work, to problematize the consequences linked to the violation of human rights and human dignity. In this process, we observed that the culture of relativization of situations that imply a violation of human rights was, at that time, abandoned. The attitude towards formative experience has turned to sensitivity to the human condition.